2013
DOI: 10.1007/s13762-013-0298-9
|View full text |Cite
|
Sign up to set email alerts
|

Predominant hosting lead(II) in ternary mixtures of heavy metal ions by a novel of diethylaminomethyl-calix[4]resorcinarene

Abstract: Heavy metal ions from single and ternary systems of Pb(II), Cu(II), and Ni(II) adsorbed by calix [4]resorcinarenes in water-chloroform extraction were studied. Comparison was made of calix [4]resorcinarenes, 2,8,14, 20-tetraundecyl calix[4]resorcinarene-4,6,10,12,16,18,22,24-octol, and diethylaminomethyl-calix[4]resorcinarene, 5,11, 17,23-tetra(diethylaminomethyl)-2,8,14,20-tetraundecylcalix[4]resorcinarene-4,6,10,12,16,18,22,24-octol, for predominant extraction of their ions from the ternary mixture of aque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The aim of this study was to investigate the existence of lead in fish (white soles) and oyster muscle tissues in Bandar Abbas watershed. The measurement of lead ions, as a main factor of polluting and destroying the environment, has been paid more attention than that of other heavy metal contaminants such as silver, zinc, and manganese (Kakavandi et al, 2017;Yusof et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study was to investigate the existence of lead in fish (white soles) and oyster muscle tissues in Bandar Abbas watershed. The measurement of lead ions, as a main factor of polluting and destroying the environment, has been paid more attention than that of other heavy metal contaminants such as silver, zinc, and manganese (Kakavandi et al, 2017;Yusof et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Calixarenes, resorcinarenes, macrocyclic cavitands extensively studied for host-guest applications, [23][24][25][26] are well known for their ability to bind molecular guests via noncovalent interactions within their shallow and well-defined bowl-shaped cavity. 27 Two-component dimeric and hexameric capsules are common [28][29][30] but three-component all-organic structures involving macrocycles remain rare, and mostly involve either the host supported on a polymer or surface or polymer-like backbone, [31][32][33][34] or the host forming an inclusion complex with two guests simultaneously. [35][36][37][38][39] But research into these systems has overlooked a potentially useful topology.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the aromatic phenolic rings can form a cavity to integrate the guest metal ion. Recently, Yusof et al reported that the heavy metal ions could be included into the host calix[4]resorcinarenes cavity in water-chloroform extraction systems [ 4 , 5 ]. Calix[6]arenes can be also modified with a carboxylic acid as host in the host – guest extraction of immunoglobulin G (IgG) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%